Optimal selection test of material ratio in the top of Ordovician limestone grouting reconstruction - Zhenli FAN; Lutong CAO; Fengda ZHANG; Xiwen YIN; Qiuyang ZHAO; Zhiwei ZHANG (Meitan kexue jishu)
It is an effective method to reduce the risk of floor water inrush by grouting reconstruction and sealing of water channel on top of Ordovician limestone before deep confined water mining in Huabei type coal mine in China. The basic properties of fly-ash cement materials with different ratios were tested using the orthogonal test method, in accordance with the requirements of deep medium to strong pervious limestone grouting project in Zhuozishan coal field. Subsequently, the influences of three factors, water-solid ratio, solid ratio and temperature, on six indexes of slurry density, viscosity, water extraction rate, setting rate, setting time and mechanical strength were analyzed. The results show that the ratio of water to solid has a relatively prominent effect on 6 indexes of slurry. The solid ratio has great influence on the viscosity, setting time and mechanical strength of the slurry. The effect of temperature on the performance of the slurry is relatively small. The pressure boosting process of ground grouting holes is divided into three stages: low-pressure filling, medium-pressure diffusion, and high-pressure fracture extension and reinforcement. The grouting material ratio varies across different stages of grouting. The comprehensive balance method yielded three material ratio schemes tailored for various grouting stages. The optimal grouting material ratio is applied for the grouting renovation of medium-strong pervious limestone. Engineering practice demonstrates that the slurry effectively diffuses and fills cracks in the formation, essentially intercepting the vertical water channel exposed at the top of the Ordovician limestone. It reduces the risk of water inflow on the working face and provides technical support for regional grouting treatment projects targeting the top of the Ordovician limestone.